Uneven regulation and economic reallocation: Evidence from transparency regulation - Matthias Breuer; Patricia Breuer (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
We investigate the impact of uneven transparency regulation across countries and industries on the location of economic activity. Using two distinct sources of regulatory variation-the varying extent of financial-reporting requirements and the staggered introduction of electronic business registers in Europe-, we consistently document that direct exposure to transparency regulation is negatively associated with the focal industry's economic activity in terms of inputs (e.g., employment) and outputs (e.g., production). By contrast, we find that indirect exposure to supplier and customer industries' transparency regulation is positively associated with the focal industry's economic activity. Our evidence suggests uneven transparency regulation can reallocate economic activity from regulated toward unregulated countries and industries, distorting the location of economic activity.
Keywords: K22; L51; M21; M41; M48; 330; Regulation; Reallocation; Transparency; Disclosure; Supply Chain